Modeling the adoption of personal health record (PHR) among individual: the effect of health-care technology self-efficacy and gender concern. Issue 1 (1st January 2018) - Dutta, Bireswar; Peng, Mei-Hui; Sun, Shu-Lung
ABSTRACT: Background : With the development of information technology (IT) and medical technology, medical information has been developed from traditional paper-based records into up-to-date medical information exchange system called personal health record (PHR). Empowering PHR provides health awareness and intention for health promotion. Objective : The purpose of this study was to present a research framework to examine individuals' intention to PHR use. Methods : This cross-sectional study used the questionnaire to collect data from the individual in Taiwan. Individual's intention to use PHR has been examined by a framework based on extended technology acceptance model (TAM), with gender and health-care technology self-efficacy (HTSE) as external variables. Additionally, gender differences were explored in perceptions and relationships among factors influencing an individual's intention to PHR use. The research framework was evaluated by structural equation modeling (SEM) and represented by Analysis of a Moment Structures (AMOS). Results : A total of 234 valid responses were used for analysis. The results suggest that the extended TAM model explains 40.6% of the variance of intention to PHR use ( R 2 = 0.406). The findings also supported that perceived usefulness, perceived ease of use, and attitude toward using PHR significantly influenced individual's intention to PHR use. Additionally, results also indicated that women were more strongly influenced by perceptions of HTSE. Conclusions : The extended TAM model contributes reasonable explanation for interprets and anticipates of individuals' intention to use and adopt PHR. Moreover, the results have provided support for HTSE and gender as significant variables in TAM. However, the study identified three relevant factors directly and one factor indirectly influencing on individuals' intention to PHR use. Thus, health care providers and hospital authorities must take these factors and gender difference into consideration in the development and validation of the theories regarding the acceptance of PHR. Based on the findings, the theoretical and practical implications are discussed.